Employment in agriculture: Jobs for Africa’s youth - Brooks, Karen; Zorya, Sergiy; Gautam, Amy (International Food Policy Research Institute, 2013)
Africa south of the Sahara has the world’s fastest growing population and the youngest. By 2050 the subcontinent, with its projected 1.7 billion people, will be the second most populous region in the world, after South Asia, and the only region in which the rural population will still be growing. Between 2010 and 2050 other regions will experience a significant decrease in rural population (which will fall by 50 percent in East Asia, 45 percent in Europe, and 10 percent in South Asia), while Africa south of the Sahara will add an estimated 150 million people in rural areas (an increase of nearly 30 percent). The young people yet to be born are in addition to the 330 million already present and about to enter the labor force, of whom 195 million live in rural areas.1 As Figure 1 shows, the number of people entering rural labor markets each year is projected to increase until at least 2035.